Encapsulated bioactive compounds-rich powders: preparation of a non-alcoholic beverage from amazon species - Mar, Josiana Moreira (2019)
Interest in the discovery of new antioxidants through unconventional food plants (UFP) has been growing mainly to prevent food deterioration and minimize harm to human health. The Amazon region is known for its rich biodiversity, with several fruit species presenting high amounts of bioactive compounds. In the Chapter 3, the effects of different drying methods (freeze- or spray- drying) and carriers (gum Arabic or inulin) on the powder characterization and stability of the bioactive compounds of Hibiscus acetosella extract (HAE) during storage were evaluated. The 1H NMR spectrum of the HAE revealed characteristic signals of the caffeoyl hydroxycitric acid. The encapsulated extract powder presented different morphology according to the drying processes. Powders produced by the freeze-drying process presented higher retention of bioactive compounds due to the low temperature process. The mixture of gum Arabic and inulin as carrier resulted in the absorption of larger amount of water. The half-life time of the encapsulated extract powders ranged from 31 – 36 h (DPPH) and from 34 – 71 h (phenolic compounds). In general, the powders constituted of gum Arabic and produced by the freeze- drying process presented better protection and retention of the bioactive compounds from the HAE. The Chapter 4 reports the encapsulation of bioactive compounds from Clidemia japurensis and Clidemia hirta juices in maltodextrin of different dextrose equivalents (DE). Microparticles containing the encapsulated juices were obtained by freeze-drying process. The stability of the encapsulated bioactive compounds was evaluated under different relative humidity (22 and 77%) at 25 °C by DPPH and ABTS methods. Twelve bioactive compounds were identified by UFLC-Q-TOF- MS/MS and classified as organic acids, flavonoids and anthocyanins. The juices presented good antioxidant properties [DPPH value of 943 ± 15 µM TE (C. japurensis) and 994 ± 14 µM TE (C. hirta); ABTS value of 1119 ± 24 µM TE (C. japurensis) and 1273 ± 18 µM TE (C. hirta)]. Encapsulation Efficiency (EE) ranged from 97.0 to 99.8% (DPPH) and from 87.8 to 99.1% (ABTS). The encapsulated juices did not present Water Activity (WA) values that could favor microbial growth. According to the ABTS results, the bioactive compounds of C. hirta and C. japurensis encapsulated in MD10 wall material and stored at RH = 22% presented half-life time around 45 and 37 days, respectively. These results represent an interesting possibility of application in food industry.